EVALUATION OF THE IMPLEMENTATION OF THE MIDDLE CLASS SUNDAY SCHOOL CURRICULUM WITH THE CIPP APPROACH AT THE GPSDI EFATA AMBON CONGREGATION - Sifera Sampe Liling; Herly Janet Lesilolo; Yowelna Tarumaselly; Sephliano Elrianto Maxnusiz Sahureka; Dritin Isfhanavia (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This study evaluates the implementation of the Middle Grade Sunday School Curriculum at GPSDI Jemaat Efata Ambon using the CIPP (Context, Input, Process, Product) approach. The evaluation was conducted using a mixed method, combining quantitative data from 32 students through questionnaires and qualitative data through in-depth interviews, observations, and documentation of teachers, administrators, parents, and students. The evaluation results indicate that the learning context and the suitability of the curriculum to the needs of children aged 9–11 years still need adjustments to be more relevant and participatory. Input aspects such as teaching materials, media, teacher competency, and infrastructure are in the inadequate category, thus limiting the effectiveness of the learning process which tends to be lecture-dominated and minimal interactivity. Product evaluation shows growth in faith, skills in leading prayer and praise, but mastery of memorized verses is not consistent. These findings emphasize the need for more adaptive curriculum improvements, teacher competency enhancement, utilization of learning media, and integration of formative evaluation to support the growth of faith, character, and students' skills on an ongoing basis. This study provides a practical contribution to the development of Sunday Schools in Pentecostal churches and strengthens the understanding of CIPP-based curriculum evaluation in Christian education.